Human polyomavirus BKPyV and JCPyV serostatus has no impact on women´s human papillomavirus infection outcome - Laine, Hanna K.; Waterboer, Tim; Syrjänen, Kari; Grenman, Seija; Louvanto, Karolina; Syrjänen, Stina (Frontiers in Cellular and Infection Microbiology, 2023)
Polyomaviruses have both structural and functional similarities with papillomaviruses. Accordingly, their role in human papillomavirus (HPV) associated malignancies has been studied with conflicting results. Our goal was to disclose any association between BK (BKPyV) and/or JC (JCPyV) polyomavirus serology and HPV data derived from Finnish women (327) in a 6-year prospective follow-up. Glutathione S-transferase fusion-protein-capture (ELISA) in combination with fluorescent bead technology was used to analyze antibodies to BKPyV and JCPyV. In the longitudinal setting, BKPyV or JCPyV serostatus was related to i) oral- and ii) genital low (LR)- and high risk (HR) HPV DNA detection, iii) HPV16 persistence at both these sites, iv) results of the Pap (Papanicolaou) smear taken at baseline, and v) development of incident CIN (cervical intraepithelial neoplasia) during the follow-up. Being BKPyV or JCPyV seropositive was not significantly associated with HPV seropositivity to either LR- or HR-genotypes, genital- or oral HPV DNA positivity, persistence of genital- or oral HPV16 infection, grade of Pap smear, or development of incident CIN. Thus, the present study could not provide any confirmation to the concept that co-infections by HPyV and HPV have interactions that impact on the clinical manifestations or outcomes of HPV infections either in the genital tract or in the oral mucosa.